Übergänge zur Schriftlichkeit. Zu wechselnden Profilen dialektaler Literalität am Beispiel des Niederdeutschen - Langhanke, Robert (Linguistik Online, 2017)
Different types of Low German literacy create varieties in addition to spoken Low German. Their function differs according to the change of language use. By setting the focus on dialectal literature it becomes clear, which concepts of Low German literature became influential since the 19th century. In the recent situation, new perspectives for Low German and its literature can be found in the field of planned language acquisition for example at school. Therefore written forms of Low German become much more important than usually thought of by looking at the ideas of language policy and the development at schools in Northern Germany.